In-hospital Outcome of Acute Coronary Syndrome Patients with on-Admission Hyponatremia - Ali, Mohammad; Chowdhury, Abdul Wadud; Sabah, Khandker Md Nurus; Amin, Md Gaffar; Sarker, Sudhakar; Saha, Bishnu Pada; Haque, Md Mashba Ul; Farjana, Jinat (Cardiovascular Journal, 2019)
Background: Coronary artery disease is the commonest form of heart disease and the leading cause of morbidity and mortality throughout the world. Electrolytes imbalance can lead to increase in hospital mortality and morbidity in acute coronary syndrome patients. Our objective was to find out and to compare in-hospital outcome of patients presenting with acute coronary syndrome with or without onadmission hyponatremia. Methods: A total of 336 patients were included in this study of which 59 patients were in group A (sodium level <135 mmol/l). Group A was subdivided in Group A1 (Na+-134-130mmol/l), Group A2 (Na+-120- 129mmol/l), Group A3 (Na+-<120mmol/l) and 277 patients were in group B (sodium level >135 mmol/l). Results: On-admission hyponatremia was documented in 16.12 %( 59) of patients with acute coronary syndrome. Among them, 16 patients with acute anterior STEMI, 19 patients with acute inferior STEMI, 19 patients with NSTEMI and 5 patients with unstable angina. In this study, in hospital complications like acute heart failure (81.4% vs. 29.2%, p<0.05), cardiogenic shock (32.2% vs. 15.5%, p<0.05) and in hospital mortality (6.8% vs. 1.1%, p<0.05) were significantly more in the patients with hyponatremia. The frequency of in hospital mortality, acute heart failure and arrhythmia progressively increased with increasing severity of hyponatremia. Logistic regression analysis showed low plasma sodium level was independently associated with in hospital mortality (â =2.13, P =0.027, OR = 8.388, 95% CI 1.268 - 55.488). Conclusion: In this study on-admission hyponatremia significantly associated with high in-hospital adverse outcome in acute coronary syndrome patients. Cardiovasc. j. 2019; 11(2): 139-146